Аналітична модель функціонування call-центру - Коба, О.В.; Пустова, С.В. ("Доповіді НАН України", 2007)
An analytical model of the call center operation is developed as a retrial queueing system M/M/c with abandons. The main characteristics of an effective call center operation are defined, and some graphical dependences and numerical characteristics are given.